Peace and Understanding: A Ricoeurian Perspective - Timo Helenius; Björn (Approaching Religion)
Persistent and newly emerging conflicts around the world have made the search for successful conflict resolution imperative. We need insights into how to prevent violent clashes, and how to find ways to peace and reconciliation. Since the 1970s, an increasing number of institutions have started to work on topics such as “peace studies”, “conflict resolution/transformation”, “transitional justice”, and “reconciliation”. The articles published in this issue are based on keynote lectures and presentations held at the workshop “Peace and Understanding: A Ricœurian View” that took place at Åbo Akademi University in Finland in September 2023. The workshop focused on the French philosopher Paul Ricœur’s contribution to the questions of war, power, violence, social justice, interreligious understanding and peace and reconciliation.